2019
DOI: 10.1016/j.lfs.2019.116950
|View full text |Cite
|
Sign up to set email alerts
|

The effect of C-peptide on diabetic nephropathy: A review of molecular mechanisms

Abstract: C-peptide is a small peptide connecting two chains of proinsulin molecule and is dissociated before the release of insulin. It is secreted in an equimolar amount to insulin from the pancreatic beta-cells into the circulation. Recent evidence demonstrates that it has other physiologic activities beyond its structural function. C-peptide modulates intracellular signaling pathways in various pathophysiologic states and, could potentially be a new therapeutic target for different disorders including diabetic compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 107 publications
2
21
1
2
Order By: Relevance
“…Remarkably, pathways analysis of EVs proteins showed that they are prevalently involved in antigen presentation by MHC class I and II, cytoskeleton remodeling, adenosine signaling, adrenergic signaling, G protein signaling and specific G protein C-peptide signaling, and lipid metabolism. C-peptide (proinsulin), prevalently studied in diabetes, exerts its biological activities via a specific G-protein coupled receptor also expressed on endothelial cells and fibroblasts [42]. Its signaling involves ERK1/2, PI3K-Akt, PKC, eNOS and NF-kB, well-known factors in TGF-β signaling [43,44], the key regulator of fibrosis, thereby suggesting C-peptide involvement in fibrogenic processes [45].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, pathways analysis of EVs proteins showed that they are prevalently involved in antigen presentation by MHC class I and II, cytoskeleton remodeling, adenosine signaling, adrenergic signaling, G protein signaling and specific G protein C-peptide signaling, and lipid metabolism. C-peptide (proinsulin), prevalently studied in diabetes, exerts its biological activities via a specific G-protein coupled receptor also expressed on endothelial cells and fibroblasts [42]. Its signaling involves ERK1/2, PI3K-Akt, PKC, eNOS and NF-kB, well-known factors in TGF-β signaling [43,44], the key regulator of fibrosis, thereby suggesting C-peptide involvement in fibrogenic processes [45].…”
Section: Discussionmentioning
confidence: 99%
“…4 Although the molecular understanding of diabetic nephropathy is expanding, its exact pathophysiology is still elusive. 5 Urinary metabolites are a direct readout of kidney function 6 and might therefore offer novel molecular insights into the pathophysiology of diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…However, because GLP-1 receptors are also abundantly represented throughout the reproductive system (26), it is has been suggested that incretins and fertility/sex hormones are also interconnected. Indeed, GLP-1 and its receptor agonists are suggested to exert positive influences on different aspects concerning fertility, such as gonadotropin-releasing hormone and leutinizing hormone release (26), polycystic ovary syndrome (26), and male testosterone production; however, results of the latter two might be confounded by the direct or indirect insulin-sensitizing effects of GLP-1 agonists (27), and it therefore remains unclear if, and to what extent, sex hormones and incretins actually affect each other directly, within or without the context of insulin sensitivity.…”
mentioning
confidence: 99%